The CAP in disarray: EU Commission proposes basic direct payments to EU farmers - Ulrich Koester (Intereconomics, 2012)
Direct payments were originally justified as a mechanism to compensate farmers for the income loss incurred due to reduced intervention prices. However, this rationale is not valid any more, and a new justification for basic income support by granting basic decoupled direct payments has been proposed by the EU Commission. The following paper identifies a number of problems related to this proposal.
Keywords: 330; EU-Agrarpolitik; Agrarsubvention; Wirkungsanalyse; EU-Staaten